PENDEKATAN POST KOLONIAL DALAM MELIHAT SEJARAH KOLONIALISME DI KALIMANTAN - Nugroho Nur Susanto (Balai Arkeologi Kalimantan Selatan, 2006)
History exist since it is presented rather than appeared of its own accord; the position of history is essential since deals with events taken place in the past and in the future. Actually,Â today one may alter the past by altering the way of thinking and how the past is interpreted. It is sensible not to be satisfied by interpretation; moreover it has been presented based onÂ the 'power' during colonialism in Kalimantan. Such 'power' will interpret an event according its own point of view. The 'post-colonial' approach is a vital tool to signify the past of Kalimantan. This approach stresses on ethnological-direct-interpretation supported by material approach such as by archaeology.